HUBUNGAN DURASI PIJAT BAYI DENGAN KUALITAS TIDUR BAYI DI DESA SILO Tahun 2019 - Wieminaty, Aldi Febrian (Program Studi Keperawatan dan Kesehatan, Sekolah Tinggi Ilmu Kesehatan (STIKES) Bhakti Al-Qodiri, 2020)
ABSTRACT Baby massage is art of medical treatment and therapy than knowing along human created in this world and have been practiced last century by hereditarily with soothsayer. The baby is a child which the old age is 0-12 months.In the Village area of South District Silo, obtained from 10 infants there were three babies who do not sleep or waking during sleep and seven other babies have to sleep soundly at night. therefore, researchers want to know is there any relationship between infants in the massage and no massage with baby sleep quality. Type of research isexperiment, research, systematic sampling with random sampling, the sample was 0-12 months old infants in the Village area Silo 36 infants. Data collected by questionnaire and data processing spread in tabulation with Chi square test. Than 50% of mothers who massage their babies in a baby who got 47.22% and 2.78% sleeping babies do not sleep soundly, and from 50% or a group of mothers who did not massage the baby was found 5.56% of babies sleep soundly and 44 , 44% of infants do not sleep soundly. After using the chi-square statistical test was found at 21.854, while the chi-square table with a dk of 3.841 (21.854> chi-square table value of 3.481), then the zero hypothesis (Ho) is rejected. Contingency coefficient and hypothesis test with the results 0,641, The strength of the relationship 0.40 <KK <0.70 Fair means or medium. Of this research is expected the mothers to massage their babies with a good and loving on her baby.